Molecular and Functional Profiles of Exosomes From HPV(+) and HPV(−) Head and Neck Cancer Cell Lines - Ludwig, Sonja; Sharma, Priyanka; Theodoraki, Marie-Nicole; Pietrowska, Monika; Yerneni, Saigopalakrishna S.; Lang, Stephan; Ferrone, Soldano; Whiteside, Theresa L. (Frontiers in Oncology, 2018)
Exosomes produced by tumor cells have been shown to reprogram functions of human immune cells. Molecular cargos of exosomes isolated from supernatants of HPV(+) and HPV(−) head and neck cancer (HNC) cell lines or from HNC patients' plasma were compared. The exosome protein profiles resembled those of respective parent tumor cells. Only HPV(+) exosomes carried E6/E7, p16, and survivin. HPV(−) exosomes were negative for cyclin D1 and carried low p53 levels. Immunomodulatory molecules (TGF-β, FasL, OX40, OX40L, and HSP70) were carried by HPV(+) and HPV(−) exosomes. These exosomes co-incubated with human T cells induced apoptosis and suppressed T cell activation and proliferation. HPV(−) exosomes suppressed DC maturation and expression of antigen processing machinery (APM) components. In contrast, HPV(+) exosomes promoted DC maturation and did not suppress expression of APM components in mature DCs. While DCs readily internalized exosomes, T lymphocytes resisted their uptake during the initial 12 h co-culture. Thus, HPV(+) exosomes capable of sustaining DC functions may play a key role in promoting anti-tumor immune responses thereby improving outcome in patients with HPV(+) cancers.